Mesenchymal Stromal Cell-Based Bone Regeneration Therapies: From Cell Transplantation and Tissue Engineering to Therapeutic Secretomes and Extracellular Vesicles - Marolt Presen, Darja; Traweger, Andreas; Gimona, Mario; Redl, Heinz (Frontiers in Bioengineering and Biotechnology, 2019)
Effective regeneration of bone defects often presents significant challenges, particularly in patients with decreased tissue regeneration capacity due to extensive trauma, disease, and/or advanced age. A number of studies have focused on enhancing bone regeneration by applying mesenchymal stromal cells (MSCs) or MSC-based bone tissue engineering strategies. However, translation of these approaches from basic research findings to clinical use has been hampered by the limited understanding of MSC therapeutic actions and complexities, as well as costs related to the manufacturing, regulatory approval, and clinical use of living cells and engineered tissues. More recently, a shift from the view of MSCs directly contributing to tissue regeneration towards appreciating MSCs as “cell factories” that secrete a variety of bioactive molecules and extracellular vesicles with trophic and immunomodulatory activities has steered research into new MSC-based, “cell-free” therapeutic modalities. The current review recapitulates recent developments, challenges, and future perspectives of these various MSC-based bone tissue engineering and regeneration strategies.